Swedish Hydroclimatic Data 1961-2020 – Precipitation, Temperature and Streamflow Observations across 50 Catchments (CAMELS-SE) - Teutschbein, Claudia (Uppsala University, 2024)
This community-accessible dataset comprises daily hydroclimatic variables (precipitation, temperature, and streamflow) observed across 50 catchments in Sweden. The dataset covers a 60-year period (1961-2020) and includes information on geographical location, landcover, soil types, hydrologic signatures, and regulation for each catchment.

Data was collected from various sources, such as the Swedish Meteorological and Hydrological Institute (SMHI), the Swedish Geological Survey (SGU) and several Copernicus products provided by the European Environment Agency. The compiled, spatially-matched, and processed data is publicly available online.

The dataset spans two designated 'climate normal periods' (CNPs): 1961-1990 and 1991-2020, and a wide range of hydroclimatic, topographic and environmental catchment properties, making it a valuable resource for researchers and practitioners to gain in-depth insights into hydrological processes, explore climate change impacts, and devise sustainable water management strategies. With its long record period and versatility, the dataset is a great resource for model calibration, education, method development, and fostering transdisciplinary research across various disciplines.

Datamängden består av dagliga observationer av nederbörd, temperatur och avrinning för 50 avrinningsområden i Sverige över en 60-årsperiod (1961-2020). Utöver dessa observationer innehåller datamängden även information om geografiskt läge, marktäckning, jordtyper, hydrologiska signaturer och reglering för varje avrinningsområde.
Informationen samlades in från olika källor, inklusive Sveriges meteorologiska och hydrologiska institut (SMHI), Sveriges geologiska undersökning (SGU) samt flera Copernicus-produkter som tillhandahölls av European Environment Agency. De sammanställda, geografiskt matchade och bearbetade uppgifterna är tillgängliga online.
Datasetet omfattar två definierade "klimatnormalperioder": 1961-1990 och 1991-2020 och innehåller en bred variation av hydroklimatiska, topografiska och miljömässiga egenskaper, vilket gör det till en ovärderlig resurs för både forskare och praktiker. Det kan ge insikter i hydrologiska processer, möjliggör utforskning av klimatförändringars påverkan samt stödjer utformningen av hållbara strategier för vattenförvaltning.
På grund av den långa tidsperioden lämpar sig datasetet för kalibrering av modeller, utbildning, metodutveckling och främjar tvärvetenskaplig forskning över olika discipliner. Det utgör en viktig grund för att förstå och hantera vattenrelaterade utmaningar i en föränderlig miljö.
Hydroklimatiska förhållanden i Sverige 1961-2020 - Nederbörd, temperatur och avrinningsobservationer i 50 avrinningsområden (CAMELS-SE)
Keywords: SURFACE TEMPERATURE; PRECIPITATION INDICATORS; catchment area; avrinningsområde; water runoff; air temperature; lufttemperatur; catchment; upptagningsområde; watershed; mean annual temperature; mean annual precipitation; river basin; temperature; river discharge; streamflow; surface runoff; precipitation amount; river; hydrology; hydrologi; precipitation; catchment scale; climate; klimat; climate change; river station; Hydrography; Hydrografi; catchment areas; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Climate Science; Klimatvetenskap; Environmental Sciences; Miljövetenskap; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Boundaries; Administrativa gränser; Geoscientific Information; Geovetenskap; Climatology / Meteorology / Atmosphere; Klimatologi och meteorologi; Location; Positionering; Inland Waters; Sjöar och vattendrag